2002
DOI: 10.1002/app.11446
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristics of composites of high‐crystalline cellulose with polypropylene: Effects of maleated polypropylene and cellulose content

Abstract: Binary composites of high-crystalline fibrous cellulose with polypropylene (PP) or maleic anhydridegrafted polypropylene (MAPP) were prepared by melt-mixing with different contents of cellulose from 0 to 60 wt %. Ternary composites of cellulose with PP and MAPP were also prepared to investigate the effects of MAPP as a compatibilizer between cellulose and PP. Scanning electron microscopy revealed that the addition of MAPP generates strong interactions between a PP matrix and cellulose fibers: All cellulose fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 30 publications
10
110
0
Order By: Relevance
“…Niska and Sain (2008) and Qiu et al (2003) experienced similar improvements to the tensile strength after the addition of 2 wt.% PPgMA to 50% wood flour-PP composites, and the addition of PPgMA to high-crystalline fibrous cellulose-PP composites, respectively. It has been shown that PPgMA forms covalent linkages between maleic anhydride groups and hydroxyl groups on the cellulosic portions of natural fibers (Hedenberg and Gatenholm 1995).…”
Section: Effect Of the Compatibilizer On The Propertiesmentioning
confidence: 75%
“…Niska and Sain (2008) and Qiu et al (2003) experienced similar improvements to the tensile strength after the addition of 2 wt.% PPgMA to 50% wood flour-PP composites, and the addition of PPgMA to high-crystalline fibrous cellulose-PP composites, respectively. It has been shown that PPgMA forms covalent linkages between maleic anhydride groups and hydroxyl groups on the cellulosic portions of natural fibers (Hedenberg and Gatenholm 1995).…”
Section: Effect Of the Compatibilizer On The Propertiesmentioning
confidence: 75%
“…With the chain scissions, a release of chain segments in amorphous region that not crystallized during the original solidification process. These segments can rearrange into a crystalline phase if they have sufficient mobility, which is called chemo-crystallization [23]. The literature reported the occurrence of this phenomenon when the polypropylene (PP) is subjected to photo-degradation [22].…”
Section: Influence Of Natural Ageing On the Morphology Changesmentioning
confidence: 99%
“…25%, was found by Bax and Müssig [32] for PLLA with 10 wt% of flax fibres. Hence, the incorporation of fillers in polymer matrix increases its stiffness by restraining the chain movement and because of the high stiffness of cellulose [59]. The Charpy impact strength values of neat PLA and PLA-based biocomposite are reported in Table 4.…”
Section: Thermal Propertiesmentioning
confidence: 99%